AI Utilizations in Healthcare: Discovering New Methods for Cancer Treatment and Petroleum Fraud Mitigation - Alexandra Harry (Information Technology and Science (ITScience), 2024)
This article explores how artificial intelligence (AI) is revolutionizing two important industries: healthcare and the detection of petroleum fraud. The application of AI technology promises to improve patient care, operational effectiveness, and decision-making as they develop further. Through individualized therapies, increased diagnostic precision, and optimized operations, machine learning and data analytics can transform patient management in the healthcare industry. Examples of such applications are IBM Watson for Oncology, Google Deep Mind’s diagnostic systems, and PathAI. To fully utilize AI in healthcare, issues including algorithmic bias, data privacy, and regulatory compliance must be resolved. Leading firms in the petroleum sector, including Shell, BP, and Equinor, have implemented AI-driven fraud detection systems to monitor supply chains, analyze transaction data, and evaluate risks in order to enhance operational transparency and financial integrity. The industry's security is further improved by the combination of block chain technology and artificial intelligence. Organizations, however, have difficulties with data quality, moral dilemmas, and the requirement for ongoing AI system development. A strong framework centered on data integrity, stakeholder participation, and ethical behaviors is required for the successful application of AI in both industries. Organizations may successfully manage today's problems by adopting interdisciplinary collaboration and learning from case studies, which will ultimately improve patient outcomes, operational integrity, and service delivery. This essay demonstrates the profound effects of AI in a variety of fields and stresses the necessity of responsible and creative uses to promote a more effective, open, and just future.